Gendering the International Asylum and Refugee Debate - Freedman, J. author. aut Link
VII, 216 p.
Keywords: This study provides a comprehensive account of the situation of women refugees globally and explains how they differ from men. It looks at causes of refugee flows, international laws and conventions and their application, the policies and legislation of Western governments, and lived experiences of the refugees themselves.